Preliminary analysis of farm workers perception about continous education system in the Region of Murcia - López Lluch, David Bernardo; Zapata, Javier Lorenzo; del Campo Gomis, Francisco José (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
The objective of this work is to make an approach to the Murcia agriculture workers’ perception on the continuous training system implanted in this autonomous community. There has been a survey of a sample of these workers. It highlights the poor basic education of these workers both farm holders and workers. There is a general lack of specific training. In addition, it must be highlighted the low valuation that workers give to the continuing training system since most of them state they do it because it is compulsory.